Incisional hernia: predictive factors, clinical presentation and management - Daware, Ankit; Akhtar, Murtaza; Zaki, Bellary Mohammad (International Surgery Journal, 2019)
Background: Incisional hernia is an iatrogenic complication of abdominal surgery and an important cause of morbidity. It occurs in 11-20% of the patients after abdominal surgery. The present study aimed to evaluate predictive factors associated with causation of incisional hernia, clinical presentation, modalities of management and their post-operative complications.Methods: In a hospital based observational study, the subjects were diagnosed cases of incisional hernias with or without comorbidities undergoing planned or emergency surgeries. Patients unfit for anaesthesia were excluded. Predictive factors studied were multiparity, obesity, diabetes mellitus, postoperative wound infection, retention of urine and cough. Time of onset of incisional hernia after initial abdominal surgery, type of abdominal incision was recorded. Local examination of hernia was done to record the position, size, cough impulse, and reducibility of hernia. Patients were either managed by open or laparoscopic approach which was compared with respect to post-repair complications and recurrence.Results: Total of 64 patients were enrolled with mean age of 48.3 and SD ± 8.82 years. Incisional hernia was more common in middle-aged patients (31-50 yrs) and in females. Majority of hernias have occurred within one year (73.43%) of previous surgery. Commonest predictive factors were midline high BMI (87.5%), multiparity (64.06%), infraumbilical incision (59.37%) and postoperative surgical site infection (56.25%). Laparoscopic repair was done in 5 patients (7.83%) and was not associated with any complications while in rest 59 patients (92.17%) treated by open repair, seroma and SSI were common complications. On mean follow up of 34.8months there was 1 recurrence observed in open onlay repair.Conclusions:Middle age females with multiparity with BMI>25 having midline infraumbilical incision with history of SSI commonly developed incisional hernia in first year of previous surgery. Laparoscopic repair had no complications or recurrence.